(untitled) (Research, Society and Development, 2020)
Heat stroke is an atmospheric parameter of great local and temporal variability. The objective was to analyze and determine the average and historical values ​​of heat stroke, in the period from 1962 to 2019, for the municipalities of Recife, Surubim, Garanhuns, Arcoverde, Triunfo, Cabrobó, Petrolina, and Ouricuri. Data on monthly and annual sunshine were provided by the National Institute of Meteorology, homogenization, consistency and filling of faults in each series and their spatial and temporal density were performed. The average heat stroke for each municipality and its historical average were calculated and the necessary analyzes were carried out. The spatial distribution of the solarimetric data showed great variability for the months studied, with fluctuations of 3 to 4 hours in the monthly distribution. The median values ​​are the most likely to occur over the months for the eight municipalities under study. The municipality of Garanhuns presented higher insolation values ​​than Petrolina. Comparing the values ​​obtained in this article with the values ​​of the Solarimetric Atlas of Brazil, a good similarity of the recorded data was obtained.